Substitution of natural stony material aggregates in conventional 17.5 mpa non-structural concrete mixtures by means of percentage addition of hospital solid waste (2018)
An experimental character research was carried out. A conventional concrete mixture was made with the mechanical resistance to compression of 17.5 Mpa. The materials used in the concrete mixture were analyzed and selected based on the parameters established in the Colombian Technical Standards and the ASTM International Standards. They were made 6 test cylinders with the mentioned concrete mixture to which, the compressive strength of the concrete was checked it, 3 of them 7 days after they were made and the rest of them 28 days later, respectively. Thereafter, their drying process by immersion, the data thrown by the tests were averaged and tabulated. The Hospital waste solid incinerated and treated by Ecosteryl machine which is located at Guayabal environmental technology park in Cucuta city was collected. The material resulting from the incineration and treatment of the hospital solid waste was selected taking only the particles equal to or less than 20mm resulting from the crushing process by Ecosteryl. With the selected Particulate material, 3 experimental mix designs were made, which 2.5, 5 and 7.5% of the total weight of the natural stone aggregates present in the conventional concrete mixture was replaced. With each experimental mixture made, 6 cylinders were tested at 7 and 28 days, a process carried out in the same way as that implemented in the conventional concrete mix for both tests and data collection and analysis. The comparative tables showed that the experimental mixture I, where 2.5% of the total weight of the aggregate of the conventional concrete mixture was replaced, was the one that obtained the highest compressive strength surpassing the result of the conventional concrete mixture.